SUBTITUSI TEPUNG KULIT SINGKONG TERHADAP DAYA KEMBANG, KADAR SERAT, DAN ORGANOLEPTIK PADA CHIFFON CAKE - Novi Dyah Fitriani; Wikanastri Hersoelistyorini (Universitas Muhammadiyah Semarang, 2012)
Chiffon cake cassava peel is a semi-wet processed foods, consisting of wheat flour, sugar, butter, flour and baking soda are experiencing dough with flour substitution of cassava peel. The purpose of this study to determine the effect of substitution of cassava flour in chiffon cake skin against flower power, HCN content, fiber content, and organoleptic properties. This type of research is carried out research using randomized complete block design experiment with a perfect 5 treatments, the variation of 0%, 5%, 10%, 15% and 20%. Anova statistical test, while analysis of the organoleptic properties use Friedman test. The highest fiber content is 14.64% on 20% substitution. The highestbreed power at 5% (102.5%). Not significant of substitution of cassava flour skin of the fiber content and breed power. The best of result (nature taste) are the substitution of 5%, with the criteria of a bright brown color, sweet taste, very fragrant aroma and soft texture.Keyword: peel cassava flour, cassava peel chiffon cake, the fiber content.